Inhaled Dry Powder Formulation of Tamibarotene, a Broad‐Spectrum Antiviral against Respiratory Viruses Including SARS‐CoV‐2 and Influenza Virus. Issue 7 (10th June 2021) - Liao, Qiuying; Yuan, Shuofeng; Cao, Jianli; Tang, Kaiming; Qiu, Yingshan; Seow, Han Cong; Man, Rico Chi‐Hang; Shao, Zitong; Huang, Yaoqiang; Liang, Ronghui; Chan, Jasper Fuk‐Woo; Yuen, Kwok‐Yung; et al.
Abstract: In response to the epidemic and pandemic threats caused by emerging respiratory viral infections, a safe and efficient broad‐spectrum antiviral therapy at early onset of infection can significantly improve patients' outcome. Inhaled dry powder is easy to administer and delivers antiviral agent directly to the primary site of infection, thereby minimizing systemic side effects. Here, spray freeze drying (SFD) technique is employed to formulate tamibarotene, a retinoid derivative with broad‐spectrum antiviral activity, as inhalable powder. The SFD tamibarotene powder exhibits desirable physicochemical and aerodynamic properties for inhalation. Pulmonary delivery of tamibarotene powder results in rapid absorption and higher bioavailability compared with intraperitoneal injection of unformulated drug in animals. More importantly, inhalation or intranasal delivery of SFD tamibarotene formulation displays broad‐spectrum antiviral activity against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), Middle East respiratory syndrome coronavirus, and pandemic 2009 influenza A virus (H1N1) in mouse and hamster models by targeting lower or upper airways, and the efficacy is comparable or superior to the commercially available antivirals remdesivir and zanamivir against specific virus. These results present a promising strategy to combat various respiratory viral infections including SARS‐CoV‐2 and influenza virus, or even co‐infection. Abstract : An inhalable powder formulation of tamibarotene with hydroxypropyl‐β‐cyclodextrin as the sole excipient is developed by spray freeze drying as an inhalation therapy for respiratory viral infections. By demonstrating its broad‐spectrum antiviral efficacy against coronaviruses and influenza A viruses in vivo, this inhaled powder formulation presents a promising strategy to combat pandemic, epidemic, and seasonal respiratory viral infections.